2019
DOI: 10.1016/j.aim.2018.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Proof mining and effective bounds in differential polynomial rings

Abstract: Using the functional interpretation from proof theory, we analyze nonconstructive proofs of several central theorems about polynomial and differential polynomial rings. We extract effective bounds, some of which are new to the literature, from the resulting proofs. In the process we discuss the constructive content of Noetherian rings and the Nullstellensatz in both the classical and differential settings. Sufficient background is given to understand the proof-theoretic and differentialalgebraic framework of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Remark 3.4. In [27], Theorem 2.5, we call this fact "internal flatness" because it is equivalent to flatness of extensions of polynomial rings by internal polynomial rings in the sense of nonstandard analysis. [2] refers to such results as "effective flatness".…”
Section: Bounds On Solutions To Linear Equations In Polynomial Ringsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 3.4. In [27], Theorem 2.5, we call this fact "internal flatness" because it is equivalent to flatness of extensions of polynomial rings by internal polynomial rings in the sense of nonstandard analysis. [2] refers to such results as "effective flatness".…”
Section: Bounds On Solutions To Linear Equations In Polynomial Ringsmentioning
confidence: 99%
“…Abstract results from proof theory [17,29] suggest that it is possible to extract explicit bounds from proofs that use ultraproducts. The authors demonstrated [27] that such methods can be used to extract explicit bounds from ultraproduct proofs in commutative and differential algebra [14] [30]. (For instance, in Theorem 2.8 and Lemma 7.7 of [27] we gave another bound on b(n, d), but that bound was not polynomial in the degree of the generators.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive background to the area is presented in [17], and the survey papers [18,24] provide a good overview of some of the many applications in analysis. Proof mining continues to be expanded to new areas of mathematics: In recent years this includes pursuit-evasion games [23], differential algebra [29] and Tauberian theory [28].…”
Section: Introductionmentioning
confidence: 99%
“…The program was initiated in earnest by Ulrich Kohlenbach (who laid out its theoretical basis in [12]) and has been quite successful in some parts of analysis (see the book [13] and the more recent [15]). Recently, it was also used successfully in algebra [18] to extract uniform bounds whose existence was first established using nonstandard methods in [20] and [10].…”
mentioning
confidence: 99%